Actinobacillus actinomycetemcomitans lipopolysaccharide-mediated experimental bone loss model for aggressive periodontitis - Rogers, Jill E.; Li, Fei; Coatney, Derek D.; Rossa, Carlos; Bronson, Paul; Krieder, Jaclynn M.; Giannobile, William V.; Kirkwood, Keith L. (Amer Acad Periodontology, 2007)
Background: Bacterial constituents, such as Gram-negative derived lipopolysaccharide (LPS), can initiate inflammatory bone loss through induction of host-derived inflammatory cytokines. The aim of this study was to establish a model of aggressive inflammatory alveolar bone loss in rats using LPS derived from the periodontal pathogen Actinobacillus actinomycetemcomitans.Methods: Eighteen female Sprague-Dawley rats were divided into LPS test (N = 12) and saline control (N = 6) groups. All artimals received injections to the palatal molar gingiva three times per week for 8 weeks. At 8 weeks, linear and volumetric alveolar bone loss was measured by micro-computed tomography (mu CT). The prevalence of inflammatory infiltrate, proinflammatory cytokines, and osteoclasts was assessed from hematoxylin and eosin, immunohistochemical, or tartrate-resistant acid phosphatase (TRAP)-stained sections. Statistical analysis was performed.Results: A. actinomycetemcomitans LPS induced severe bone loss over 8 weeks, whereas control groups were unchanged. Linear and volumetric analysis of maxillae by mu CT indicated significant loss of bone with LPS, administration. Histologic examination revealed increased inflammatory infiltrate, significantly increased immunostaining for interleukin IL-6 and -1 beta and tumor necrosis factor-alpha, and more TRAP-positive osteoclasts in the LPS group compared to controls.Conclusion: Oral injections of LPS derived from the periodontal pathogen A. actinomycetemcomitans can induce severe alveolar bone loss and proinflammatory cytokine production in rats by 8 weeks.
Keywords: Actinobacillus actinomycetemcomitans; cytokines; inflammation; lipopolysaccharide; periodontal diseases